FORMULASI GRANUL EFFERVESCENT EKSTRAK ETANOL KULIT BUAH PEPAYA (Carica papaya L.) - Arianti Safitri (Jurnal Komunitas Farmasi Nasional, 2021)
Papaya fruit of peel (Carica papaya L.) is one of the plants that contains antioxidants. Where the antioxidant activity of papaya fruit ethanol extract (IC50 95,824 ppm) is classified in the strong category. This research aims to formulate effervescent granules from papaya bark ethanol extract with wet granulation method and to find out the effervescent granule formula of papaya bark extract which produces the best properties. Papaya fruit rind macerated using 96% ethanol solvent. Then papaya bark extract is formulated in 3 formulas by varying the citric acid in formula I with a concentration of 10%, formula II 12.75%, formula III 14%, tartric acid in formula I with a concentration of 20%, formula II 25.5%, formula III 28%, and sodium bicarbonate in formula I with a concentration of 25%, formula II 37.5%, formula III 50%. The results showed formula I in the preparation of effervescent granules of ethanol extract of papaya rind met the best physical requirements including organoleptic testing in light yellow, papaya complex, and containing sour taste, pH 5, dispersed speed 3 minutes 16 seconds, water content 3 minutes 61 seconds , flow properties 2 minutes 64 seconds and rest angle 13.49°.